1989
DOI: 10.1271/bbb1961.53.443
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a major trypsin inhibitor, FMTI-II, from foxtail millet grain.

Abstract: Amajor trypsin inhibitor was purified from the extract of the whole grain of foxtail millet, Setaria italica, to an electrophoretically homogeneous protein by conventional methods. This inhibitor (FMTI-II) has a molecular weight of 7500 and contains high levels of basic amino acids, acidic amino acids, proline, and half-cystine. FMTI-II inhibited bovine and hog trypsins in a 1 : 1 (m/m) stoichiometry: the K{ values were 3.0 x 10~1l mand 2.2 x 10~10 m, respectively. Bovine a-chymotrypsin, subtilisin BPN', hog p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…Because the K i value of the inhibitor was of the same order as the enzyme concentration, we analyzed the inhibition according to the procedure described by Tashiro et al [12], and by Laskowski and Kato [13], which have been widely used in the analysis of tightly-binding inhibitors. Residual enzyme activity was estimated from the initial linear part of fluorescence intensity increase.…”
Section: Inhibition Studymentioning
confidence: 99%
“…Because the K i value of the inhibitor was of the same order as the enzyme concentration, we analyzed the inhibition according to the procedure described by Tashiro et al [12], and by Laskowski and Kato [13], which have been widely used in the analysis of tightly-binding inhibitors. Residual enzyme activity was estimated from the initial linear part of fluorescence intensity increase.…”
Section: Inhibition Studymentioning
confidence: 99%
“…Moreover, CD spectra of these recombinant proteins were essentially identical with that of the native inhibitor (see Figure 3 for KR species), indicating that there was no major alteration in the main-chain conformation from that of the native inhibitor. Like the native inhibitor [7], r-kexstatin I and all of the mutants inhibited Kex2 proteinase and subtilisin, but not thermolysin, pepsin, chymotrypsin or cathepsin B. Titration curves for the inhibition of Kex2 proteinase and subtilisin by the native and recombinant inhibitors were best fitted to those described in terms of tight-binding competitive inhibition [12,13] (Figure 4). This is consistent with the fact that the SSI, a prototype inhibitor of the SSI family, competitively inhibits subtilisin [21].…”
Section: Rational Mutagenesis Studiesmentioning
confidence: 93%
“…Residual enzyme activity was estimated from the initial linear part of fluorescence intensitiy change (excitation, 380 nm ; emission, 460 nm), which was monitored at 25 mC with a Hitachi Fluorescence Spectrophotometer F-2000. Because preliminary studies suggested that kexstatin I was a tight-binding inhibitor whose K i values were of the same or lower order as the enzyme concentration, we analysed the inhibition according to the procedure described by Tashiro et al [12] and Laskowski and Kato [13], which has widely been used for the analysis of tightbinding inhibition. Briefly, the slopes were converted into free enzyme concentrations, which were used, together with the initial concentrations of the inhibitor, to calculate the association equilibrium constants, K a (l 1\K i ), using software devised by Professor Tashiro [12] (Department of Food Science and Nutrition, School of Human Environmental Science, Mukogawa Women's University, Nishinomiya, Hyogo, Japan) run on an NEC 9801 computer ; each titration curve was fitted to the theoretical equation of Bieth and Frechin [14] using a non-linear least-squares analysis program ; the best-fit line through the data points yielded K a .…”
Section: Inhibition Kineticsmentioning
confidence: 99%